Maternal Mosaicism Is a Significant Contributor to Discordant Sex Chromosomal Aneuploidies Associated with Noninvasive Prenatal Testing. (1st January 2014) - Wang, Yanlin; Chen, Yan; Tian, Feng; Zhang, Jianguang; Song, Zhuo; Wu, Yi; Han, Xu; Hu, Wenjing; Ma, Duan; Cram, David; Cheng, Weiwei
Abstract: BACKGROUND: In the human fetus, sex chromosome aneuploidies (SCAs) are as prevalent as the common autosomal trisomies 21, 18, and 13. Currently, most noninvasive prenatal tests (NIPTs) offer screening only for chromosomes 21, 18, and 13, because the sensitivity and specificity are markedly higher than for the sex chromosomes. Limited studies suggest that the reduced accuracy associated with detecting SCAs is due to confined placental, placental, or true fetal mosaicism. We hypothesized that an altered maternal karyotype may also be an important contributor to discordant SCA NIPT results. METHODS: We developed a rapid karyotyping method that uses massively parallel sequencing to measure the degree of chromosome mosaicism. The method was validated with DNA models mimicking XXX and XO mosaicism and then applied to maternal white blood cell (WBC) DNA from patients with discordant SCA NIPT results. RESULTS: Sequencing karyotyping detected chromosome X (ChrX) mosaicism as low as 5%, allowing an accurate assignment of the maternal X karyotype. In a prospective NIPT study, we showed that 16 (8.6%) of 181 positive SCAs were due to an abnormal maternal ChrX karyotype that masked the true contribution of the fetal ChrX DNA fraction. CONCLUSIONS: The accuracy of NIPT for ChrX and ChrY can be improved substantially by integrating the results of maternal-plasma sequencing with those for maternal-WBC sequencing. The relatively high frequency of maternal mosaicism warrants mandatory WBC testing in both shotgun sequencing– and single-nucleotide polymorphism–based clinical NIPT after the finding of a potential fetal SCA.